Gastrointestinal bleeding secondary to an incidental foreign body – a case report and literature review - Olszak, Natalia; Jamer, Tatiana; Rasiewicz, Marcin; Borys-Iwanicka, Agnieszka; Krzesiek, Elżbieta; Pytrus, Tomasz; Patkowski, Dariusz (Pediatria Polska - Polish Journal of Paediatrics, 2023)
We report the case of a 3-year-old girl who was admitted to the hospital because she had been passing tarry stools for about a month. Passing black, tarry stools is a distressing symptom and usually the result of gastrointestinal (GI) bleeding. Injury due to an ingested foreign body may be one of the causes of GI bleeding. The increasing popularity of magnetic toys in recent decades has raised the incidence of magnet ingestion in the pediatric population. Injuries caused by these objects carry a significant and potentially preventable risk of morbidity and even mortality in children. The clinical picture is variable and may include non-specific symptoms such as GI bleeding. It is important for pediatricians to consider the possibility of a foreign body in the GI tract in the diagnosis of GI bleeding and spread awareness about the danger of objects containing magnets.